Primary Larynx Cryptococcus neoformans Infection: A Distinctive Clinical Entity. (26th October 2015) - Bergeron, Mathieu; Gagné, Andrée-Anne; Côté, Mathieu; Chênevert, Jacinthe; Dubé, Robert; Pelletier, René
Abstract: Cryptococcus neoformans can directly infect the vocal cords. Endoscopic findings were undistinctive from most infiltrative diseases. Tissue biopsy was essential for the diagnosis. Inhaled corticosteroids can predispose to the infection, and fluconazole 400 mg daily for at least 6 weeks appeared to be minimal to achieve a permanent cure.